The level of chemerin and adipocyte fatty acid binding protein in Toxoplasma gondii seropositive obese individuals - Agustin Iskandar; Karomah Sriwedari; Indah Adhita Wulanda; Muhammad Rasjad Indra; Hartojo; Novi Khila Firani; Ery Olivianto (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To know the difference between chemerin and adipocyte fatty acid-binding protein (AFABP) levels in obese individuals with positive Toxoplasma gondii (T. gondii) immunoglobulin G (IgG) compared with negative T. gondii IgG. Methods: This study is a cross-sectional study by using consecutive sampling methods conducted from January to April 2013. The subjects were 57 obese individuals who were divided into obese group of positive and negative T. gondii IgG. The level of chemerin, AFABP and T. gondii IgG was done by ELISA. The data were analyzed by independent t test. Results: The results showed that the level of chemerin of positive T. gondii IgG group was significantly higher than the negative T. gondii IgG group [(70.0 ± 16.5) vs. (64.4 ± 16.1) pg/mL; P = 0.003], but there was not significant AFABP difference between seropositive and negative IgG groups [(83.6 ± 41.9) vs. (74.2 ± 36.7) pg/mL; P = 0.598]. Conclusions: It can be concluded that the level of chemerin of seropositive T. gondii IgG was higher than that in the negative T. gondii IgG group.